2015
DOI: 10.1111/liv.12776
|View full text |Cite
|
Sign up to set email alerts
|

Forns index predicts recurrence and death in patients with hepatitis B‐related hepatocellular carcinoma after curative resection

Abstract: Our data suggest that Forns index could be a useful predictor of recurrence and overall survival after curative resection of HBV-related HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 35 publications
4
19
0
Order By: Relevance
“…Zhang et al reviewed the degree of cirrhosis affecting the prognosis of patients and found that the histological severity of cirrhosis is a vital adverse factor that affects the long-term outcomes of HCC patients undergoing liver surgery [38] . Similar results have been found in many reports [39][40][41] . The effect of AFP levels on patient prognosis is controversial.…”
Section: The Establishment Of Different Risk Groups According To the supporting
confidence: 93%
“…Zhang et al reviewed the degree of cirrhosis affecting the prognosis of patients and found that the histological severity of cirrhosis is a vital adverse factor that affects the long-term outcomes of HCC patients undergoing liver surgery [38] . Similar results have been found in many reports [39][40][41] . The effect of AFP levels on patient prognosis is controversial.…”
Section: The Establishment Of Different Risk Groups According To the supporting
confidence: 93%
“…Zhang et al reviewed the degree of cirrhosis affecting the prognosis of patients and found that the histological severity of cirrhosis is a vital adverse factor that affects the long-term outcomes of HCC patients undergoing liver surgery [36] . Similar results have been found in many reports [37][38][39] . The effect of AFP levels on patient prognosis is controversial.…”
Section: Discussionsupporting
confidence: 93%
“…Forns test A study of liver fibrosis indices (APRI, FIB-4 index, and Forns index) showed that Forns index performed before HCV antiviral therapy was a predictor to identify patients with low likelihood of developing HCC after achieving a sustained virologic response [132] . Morevoer, Forns index was found to predict the recurrence and death of patients with hepatitis B-related HCC after curative resection [133] .…”
Section: Fibrosis-4 Indexmentioning
confidence: 95%